2015
DOI: 10.1149/2.0771506jes
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of a Photocatalyst of Ta4N5Nanocolumn Arrays by Using Reactive Sputtering

Abstract: This paper reports a facile fabrication method for robust and separated polycrystalline Ta 4 N 5 nanocolumn arrays on a FTO/glass substrate that involves using reactive sputtering, which provides an alternative approach to fabricating nitrides without using caustic NH 3 gases. The bandgap of Ta 4 N 5 nanocolumns made at 600 • C was observed to be approximately 2.5 eV. The excellent photodegradation performance was demonstrated in an environment with a pH of 10, in which approximately 80% of methylene blue (5 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Furthermore, a previous study demonstrated that the chemical environment (i.e., pH level) of photocatalysis is crucial for efficiency. 56 Our earlier study 24 showed that a pH value of approximately 10 was optimal for FIG. 4. AES spectra of the Ta 3 N 5 microcolumns.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, a previous study demonstrated that the chemical environment (i.e., pH level) of photocatalysis is crucial for efficiency. 56 Our earlier study 24 showed that a pH value of approximately 10 was optimal for FIG. 4. AES spectra of the Ta 3 N 5 microcolumns.…”
Section: Resultsmentioning
confidence: 97%
“…Although it has been reported that tantalum based photocatalysts (Ta 2 O 5 , [52,53] and its nitrogen substituted compounds [54,55]) can degrade MB, the mechanism of the photocatalytic activity on Ta 3 N 5 or comparing it with Ta 2 O 5 is not yet reported. A preliminary analysis of the possible mechanism of photodegradation based on reports using these and other photocatalysts used in MB photodegradation is therefore presented here first.…”
Section: Methylene Blue Oxidation Routesmentioning
confidence: 99%